Micromorphology and chemistry of mite domatia: mutualistic trait convergence and variation across eight sympatric north American species - Rosemary A. E. Glos; Abrianna J. Soule; Abigail Rose Adams; Macy Arnett; Josephine Marie Eckman; Quinn Isabella Hane; Avery Marie Logan; Emma Rose Morterud; Dominick J. Noeker; Christopher A. Talbot; William Ugorji; Elizabeth VanOstran; et al. (Symbiosis, 2026)
Mite domatia — small structures on plant leaves that house mutualistic mites — are widespread across plants yet remain relatively understudied. Here we investigate the chemistry and micromorphology of mite domatia across sympatric species of broadleaf deciduous woody species that have convergently evolved tuft-form mite domatia. Specifically, we test whether domatia display similar micromorphological and chemical properties using metabolomics and scanning electron microscopy across multiple independent sympatric lineages. To identify domatia-specific phenotypes, we also compare tissue within domatia to that of nearby leaf tissue on each of the four domatium-bearing species, and test whether species with domatia exhibit reduced chemical defense relative to species that lack domatia using four additional species that lack prominent domatia as a control. We found that domatium-bearing species had significantly lower total phenolic concentrations and lower total defense compound abundance compared to control species, consistent with an evolutionary trade-off between chemical and mutualistic defense. However, within leaves, domatium tissue chemical defense did not differ from surrounding laminar tissue. In contrast, trichome morphology showed clear convergent modification: domatium trichomes were 24–31% longer than trichomes elsewhere on the leaf, a pattern reversed in control species. Together, our findings shed light on the degree of phenotypic convergence in a widespread, ecologically important trait.

The disruption of a symbiotic sea anemone by light pollution: Non-linear effects on zooxanthellae and molecular indicators - K. Devon Lynn; Ana Queirós; Elizabeth Talbot; Thomas Mesher; Christine Pascoe; Pedro A. Quijón (Science of The Total Environment, 2025)

A sustainable blue economy may not be possible in Tanzania without cutting emissions - Ana M. Queirós; Elizabeth Talbot; Flower E. Msuya; Baraka Kuguru; Narriman Jiddawi; Shigalla Mahongo; Yohana Shaghude; Christopher Muhando; Elias Chundu; Zoe Jacobs; Sevrine Sailley; Elina A. Virtanen; et al. (Science of The Total Environment, 2024)

Innovative and practical tools for monitoring and assessing biodiversity status and impacts of multiple human pressures in marine systems - Angel Borja; Torsten Berg; Hege Gundersen; Anders Gjørwad Hagen; Kasper Hancke; Samuli Korpinen; Miguel C. Leal; Tiziana Luisetti; Iratxe Menchaca; Ciaran Murray; GerJan Piet; Sophie Pitois; et al. (Environmental Monitoring and Assessment, 2024)

Incorporating climate-readiness into fisheries management strategies - Elizabeth Talbot; Jean-Beth S. Jontila; Benjamin J. Gonzales; Roger G. Dolorosa; Edgar D. Jose; Recca Sajorne; Sevrine Sailley; Susan Kay; Ana M. Queirós (Science of The Total Environment, 2024)

Bright spots as climate‐smart marine spatial planning tools for conservation and blue growth - Ana M. Queirós; Elizabeth Talbot; Nicola J. Beaumont; Paul J. Somerfield; Susan Kay; Christine Pascoe; Simon Dedman; Jose A. Fernandes; Alexander Jueterbock; Peter I. Miller; Sevrine F. Sailley; Gianluca Sará; et al. (Global Change Biology, 2021)
Marine spatial planning that addresses ocean climate‐driven change (‘climate‐smart MSP’) is a global aspiration to support economic growth, food security and ecosystem sustainability. Ocean climate change (‘CC’) modelling may become a key decision‐support tool for MSP, but traditional modelling analysis and communication challenges prevent their broad uptake. We employed MSP‐specific ocean climate modelling analyses to inform a real‐life MSP process; addressing how nature conservation and fisheries could be adapted to CC. We found that the currently planned distribution of these activities may become unsustainable during the policy's implementation due to CC, leading to a shortfall in its sustainability and blue growth targets. Significant, climate‐driven ecosystem‐level shifts in ocean components underpinning designated sites and fishing activity were estimated, reflecting different magnitudes of shifts in benthic versus pelagic, and inshore versus offshore habitats. Supporting adaptation, we then identified: CC refugia (areas where the ecosystem remains within the boundaries of its present state); CC hotspots (where climate drives the ecosystem towards a new state, inconsistent with each sectors’ present use distribution); and for the first time, identified bright spots (areas where oceanographic processes drive range expansion opportunities that may support sustainable growth in the medium term). We thus create the means to: identify where sector‐relevant ecosystem change is attributable to CC; incorporate resilient delivery of conservation and sustainable ecosystem management aims into MSP; and to harness opportunities for blue growth where they exist. Capturing CC bright spots alongside refugia within protected areas may present important opportunities to meet sustainability targets while helping support the fishing sector in a changing climate. By capitalizing on the natural distribution of climate resilience within ocean ecosystems, such climate‐adaptive spatial management strategies could be seen as nature‐based solutions to limit the impact of CC on ocean ecosystems and dependent blue economy sectors, paving the way for climate‐smart MSP.

Towards a TDP-43-Based Biomarker for ALS and FTLD - Emily Feneberg; Elizabeth Gray; Olaf Ansorge; Kevin Talbot; Martin R. Turner (Molecular Neurobiology, 2018)